Performance, Inclusion and Excellence: An Index of Educational Achievements for PISA - Villar, Antonio (Advances in Social Sciences Research Journal, 2017)
Thispaperproposesanelementarymultidimensionalindexthatsummarizesthreerelevantaspectsoftheeducationalachievements,outofthedataprovidedbythePISAReports.Thethreeaspectsconsideredare:performance,inclusiveness,andexcellence,andwillbeapproximatedbytheaveragescoresandthedistributionofoutcomesinthedifferentlevelsofproficiency.TheIndexofEducationalAchievements(IEA)isthegeometricmeanofthenormalisedvaluesofthosethreevariables.Weanalysethedistributionofthevariablesthatapproachthosethreeaspectsandtheresultingindex,relativetothecorrespondingaveragetestscoresoftheOECDcountries.Thisindexprovidesamuchwiderdiscriminationpowerthanthemerecomparison